Enzyme-linked immunosorbent fluorescence assay and high-pressure liquid chromatography for analysis of humoral immune responses to Coxiella burnetti proteins. - Schmeer, N (1988)
A microtiter enzyme-linked immunosorbent fluorescence assay based on alkaline phosphatase conjugate and 4-methylumbelliferyl phosphate as fluorogenic substrate was developed and adapted to quantitatively analyze immunoglobulin G subclass 1 (IgG1) and IgG2 responses of vaccinated and infected cattle to proteins of Coxiella burnetii. The enzyme-linked immunosorbent fluorescence assay surpassed the conventional enzyme-linked immunosorbent assay with a 50-fold-higher sensitivity and a broader range of linear dose-response signals. Antigens of C. burnetii were purified by sodium dodecyl sulfate extraction and molecular-sieve high-pressure liquid chromatography. The purified 14-, 27-, and 30-kilodalton proteins were used as antigens without any further treatment. Vaccination with either chloroform-methanol-extracted cell residues of C. burnetii or the 27-kilodalton major surface protein evoked an early IgG2 response to the 27-kilodalton protein (2 weeks after immunization), whereas IgG2 to lipopolysaccharides of C. burnetii was detected only in the late phase (13 weeks after immunization). These results may have implications for the serodiagnosis of acute and chronic Q fever. IgG1 against these antigens was induced solely by naturally occurring C. burnetii infections, indicating that infected cattle can be distinguished from vaccinated cattle by using the enzyme-linked immunosorbent fluorescence assay and SP27 antigen.